Certain remarks to integral equations generated by the numerical-analytical method for solution of the boundary problems - Kwapisz, M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
In the paper the comparison method and the chosing of the appropriate norm of the comparison operator is used to establish the solvability of the integral-functional equation resulted by the application of the numeric-analytic method of solving of boundary value problems for ordinary differential-delay equations of the neutral type.